Motorcycle extremity injuries in South-East Nigeria: A multicenter study - Njoku Isaac Omoke; Ndubuisi Onu Onyemaechi; Omolade Ayoola Lasebikan (Nigerian Journal of Medicine, 2020)
Background: Motorcycle extremity injuries are an important public health concern in developing countries though under-reported. This study aimed to determine the pattern of motorcycle extremity injuries and identify the potential areas to facilitate preventive strategies and improved outcomes. Patients and Methods: This was a prospective study of all the patients with motorcycle injuries that visited emergency rooms of three Nigerian tertiary hospitals from February 1, 2015, to July 31, 2016. Results: Of the 587 patients with motorcycle injuries, 393 (67%) of them sustained extremity injuries. The male: female ratio was 2.3:1; the age range was 1.25–80 years with a mean of 30 ± 14 years. Motorcycle collisions with motor vehicles were the topmost mechanism of injury. The lower extremity was the most common site involved. Fractures, abrasions and lacerations were the three top injuries sustained. One hundred and seventeen (29.8%) of them were multiply injured patients. Traumatic brain injury (TBI) (23.7%) was the most common associated injury. None of the victims wore a crash helmet or extremity protective gear at the time of injury. The mean injury-hospital arrival interval was 84 h and delayed presentation to the hospital correlated with the presence of extremity fractures. The mortality rate was 2%, and TBI was involved in 87.5% of the mortalities. Conclusion: In this study, extremity injury is an important component of injury associated with motorcycle road traffic accidents. This calls for preventive strategies based on the observed pattern, and the use of extremity protective gear by motorcyclist